2002
DOI: 10.1007/s11661-002-0253-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of small deformation on abnormal grain growth in bulk Cu

Abstract: The effect of small deformation below the level (about 8 pct) required for primary recrystallization on abnormal grain growth (secondary recrystallization) has been investigated in bulk polycrystalline Cu. The starting microstructure, without any texture and with a nearly uniform grain size of 168 m, has been obtained by compressing a cylindrical Cu specimen and recrystallizing at 800 ЊC. The fully recrystallized specimen shows distinct abnormal grain growth (AGG) after heat treatment at 800 ЊC for 12 hours. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…For example, few bigger grains due to broad initial grain size distributions, [11] higher mobility boundaries due to texture, [12] or lower energy boundaries [13] can give rise to the phenomenon. Moreover, several studies [14][15][16] have reported that also small prior strains (e < 0.1) can produce abnormal grain growth during annealing both in single-phase materials and in alloys containing second-phase particles. In fact, it remains questionable if in this case the phenomenon can still be considered a case of abnormal grain growth (driven by capillarity).…”
Section: Factors Contributing To the Selective Grain Growth Processmentioning
confidence: 99%
“…For example, few bigger grains due to broad initial grain size distributions, [11] higher mobility boundaries due to texture, [12] or lower energy boundaries [13] can give rise to the phenomenon. Moreover, several studies [14][15][16] have reported that also small prior strains (e < 0.1) can produce abnormal grain growth during annealing both in single-phase materials and in alloys containing second-phase particles. In fact, it remains questionable if in this case the phenomenon can still be considered a case of abnormal grain growth (driven by capillarity).…”
Section: Factors Contributing To the Selective Grain Growth Processmentioning
confidence: 99%
“…Particularly the frequency of 3 GBs can reach almost 30% in Ni in comparison with Mackenzie value of 6 to 8% [7]. It has been demonstrated that the production method, mechanical or thermal treatment, as well as annealing in magnetic field can influence the occurrence frequency of low-and particular that of 3 GBs [1,7,10,13]. The increase of number of 3 and 9 GBs is accompanied by the marked improvement of properties [14], particularly it decreases the GB corrosion [15].…”
Section: Introductionmentioning
confidence: 99%
“…22) For metal systems, it was observed that small deformation enhanced the AGG rate. 18) When a Cu specimen that exhibited stagnant grain growth was slightly deformed, AGG readily occurred. Under conditions where AGG occurred, a small deformation caused earlier formation of abnormal grains and more grains to grow abnormally.…”
Section: Introductionmentioning
confidence: 99%